2015
DOI: 10.1063/1.4937381
|View full text |Cite
|
Sign up to set email alerts
|

Exploring mechanisms of a tropospheric archetype: CH3O2 + NO

Abstract: Methylperoxy radical (CH3O2) and nitric oxide (NO) contribute to the propagation of photochemical smog in the troposphere via the production of methoxy radical (CH3O) and nitrogen dioxide (NO2). This reaction system also furnishes trace quantities of methyl nitrate (CH3ONO2), a sink for reactive NOx species. Here, the CH3O2 + NO reaction is examined with highly reliable coupled-cluster methods. Specifically, equilibrium geometries for the reactants, products, intermediates, and transition states of the ground-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 107 publications
2
18
0
Order By: Relevance
“…The present study not only entirely reproduced the reported isomeric‐conversion and DCs around HOCH 2 NO 2 but also disclosed many other conformers and reaction channels at the levels of B3LYP/6‐31G(d) and B3LYP/6‐311++G(d,p). Related to the chemistry of the atmosphere, many studies were made for methyl nitrate 21 and methylperoxy nitrite 31 , but the isomeric forms and isomerization channels reported were essentially the same as the present study, although some DCs not treated in the present study were shown for radical‐pair processes . A similar result to this study was reported for an isomerization channel between methyl nitrate 21 and methoxy dioxaziridine 45 in connection with the reaction of triplet nitrenes with oxygen .…”
Section: Remarks On the Present Approachsupporting
confidence: 83%
See 3 more Smart Citations
“…The present study not only entirely reproduced the reported isomeric‐conversion and DCs around HOCH 2 NO 2 but also disclosed many other conformers and reaction channels at the levels of B3LYP/6‐31G(d) and B3LYP/6‐311++G(d,p). Related to the chemistry of the atmosphere, many studies were made for methyl nitrate 21 and methylperoxy nitrite 31 , but the isomeric forms and isomerization channels reported were essentially the same as the present study, although some DCs not treated in the present study were shown for radical‐pair processes . A similar result to this study was reported for an isomerization channel between methyl nitrate 21 and methoxy dioxaziridine 45 in connection with the reaction of triplet nitrenes with oxygen .…”
Section: Remarks On the Present Approachsupporting
confidence: 83%
“…As for isomerization routes at high energy regions, rigorous treatments need to be made for deeper understanding. Radical‐pair channels including CH 3 O + NO 2 have been studied in connection with methyl nitrate 21 and methyl peroxynitrite 31 . In some special cases, multi‐reference treatments as well as excited‐surface treatments including conical intersections and seams should also be taken into account.…”
Section: Remarks On the Present Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…To get those species, unrestricted methods should be employed. Atmospheric species such as methyl nitrate and methylperoxy nitrite [45][46][47] and roaming channels involving distant radical pairs [11][12][13] should be treated by an unrestricted approach, such as UB3LYP levels.…”
Section: Remarks On the Present Approachmentioning
confidence: 99%